Penerapan Model Discovery learning pada Pembelajaran Matematika SMA pada Materi Kaidah Pencacahan - Permatasari, Besse Intan; Nurismiyati, Nurismiyati; Rahadi, Nanda Maulidina (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
The discovery learning model is a type of student-oriented learning that prioritizes meaningful learning by providing opportunities for students to build knowledge independently. The application of the discovery learning model was carried out at SMA Negeri 4 Balikpapan on 35 students of XII-IPS1. This research was descriptive research with the aim of getting an overview of the implementation, activities and learning outcomes of students when applying the discovery learning model. Data was collected through observing students' implementation and activities and mathematics learning outcomes tests. The results of the research show that the implementation of the discovery learning model was carried out well, and showed an increase in student activity and learning outcomes.